Effort Estimation in Agile Software Development: The State of the Practice in Colombia - Gomez, Diana; Cubillos, Juan; Aponte, Jairo; Rojas, Edwar (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2023: Anais do XXVI Congresso Ibero-Americano em Engenharia de Software, 2023)
Effort estimation is fundamental for developing software projects and critical for their success. This paper focuses on how Colombian agile practitioners perform effort estimates in agile projects. For this purpose, we conducted an exploratory survey study that involved 60 respondents. The main findings are the following: (1) Agile practitioners prefer estimation techniques based on Expert Judgement. (2) Most of the respondents perceive that their estimates have a medium accuracy level. (3) The determining effort drivers are features of the project team and the software to be built. (4) The use of datasets for estimation is not common. (5) Most of the results of related studies are similar to ours, with differences in terms of the roles involved and the techniques used.